Thermoeconomic method for determination of optimum insulation thickness of external walls for the houses: Case study for Turkey - Güven Acar, Şenol; Kemal Öztürk, Harun; Atalay, Öner; Dombayci, Ömer Altan; Yılmaz Ulu, Eylem (Sustainable Energy Technologies and Assessments, 2017)
The increment of the population, globalization of the world, improvement in technology and the increment of the welfare level causes to increase of energy use of goods and services. Energy consumption is commonly observed to occur in four main sectors: industry, residential, transport and agriculture. Residential sector in many countries is one of the largest energy consumers. The aim of this study to determine the optimum insulation thickness of the external wall of the housing for the selected province in four different climate regions in Turkey. As the insulation material, the polystyrene and polyurethane were used in the study. The optimum insulation thickness of the external wall was calculated using thermoeconomic method considering the effect of the inflation and interest rate, which is also called as Life Cycle Cost Analysis (LCA). For two different insulation materials, the minimum thickness was calculated for warm temperate climate region and the maximum thickness was calculated in the cold climate region as accepted. Also, the maximum savings was calculated for the cold climate region and the minimum savings was calculated for the warm temperate climate region. © 2017 Elsevier Ltd